Effects of initial temperature on microbial community succession rate and volatile flavors during Baijiu fermentation process. (March 2021) - Zhang, Hongxia; Wang, Li; Wang, Heyu; Yang, Fan; Chen, Liangqiang; Hao, Fei; Lv, Xibin; Du, Hai; Xu, Yan
Graphical abstract: Highlights: During sauce-flavor Baijiu fermentation, initial temperature affects fermentation. High temperature increases total acids and reduces total esters. A higher temperature accelerates Lactobacillus increases and microbial succession. Lactobacillus / Saccharomyces key to temperature-based flavor component differences. Abstract: The importance of fermentation temperature has been highlighted as it correlates with biodiversity and microbial metabolism for a microbial community. In this study, microbial community succession and volatile flavors during sauce-flavor Baijiu fermentation at different initial temperatures (LT group: 28 ± 2 °C and HT group: 37 ± 2 °C) were investigated using Illumina Miseq sequencing and gas chromatography-mass spectrometry (GC-MS). First, we found that different initial temperatures had a significant effect on fermentation parameters ( P  < 0.001); specifically, a higher initial temperature increased the accumulation of acetic acid and decreased the production of ethanol. Second, the microbial communities were characterized by decreased α-diversity and increased β-diversity ( P  < 0.05) during heap fermentation. A higher initial temperature accelerated the increase in Lactobacillus and led to a faster microbial succession rate. Lactobacillus could be used as microbial markers of microbial succession rate in sauce-flavor Baijiu fermentation. Next, we found that acetic acid drove microbial succession under a higher fermentation temperature. Molecular ecological network analysis showed that different fermentation temperatures affected microbial interactions. The higher temperature enhanced microbial interactions of Lactobacillus . In addition, 50 volatile flavors were identified in the fermented grains. High temperature increased the content of total acid and reduced total esters, and Lactobacillus and Saccharomyces were the important microbiota related to different flavor compounds between the two groups. Collectively, altering the initial temperature led to differences in microbial succession rates and volatile flavors in the sauce-flavor Baijiu fermentation process. Therefore, these results are valuable for exploring quality control and management strategies in the spontaneous fermentation process.